Distress Tolerance Among Students Referred for Treatment Following Violation of Campus Cannabis Use Policy: Relations to Use, Problems, and Motivation. (September 2016) - Buckner, Julia D.; Jeffries, Emily R.; Terlecki, Meredith A.; Ecker, Anthony H.
Students referred to treatment after violating campus drug policies represent a high-risk group. Identification of factors related to these students' cannabis use could inform prevention and treatment efforts. Distress tolerance (DT) is negatively related to substance-related behaviors and may be related to high-risk cannabis use vulnerability factors that can impact treatment outcome. Thus, the current study tested whether DT was related to cannabis use frequency, cannabis-related problems, and motivation to change cannabis use among 88 students referred for treatment after violating campus cannabis policies. DT was robustly, negatively related to cannabis use and related problems. DT was also significantly, negatively correlated with coping, conformity, and expansion motives. DT was directly and indirectly related to cannabis problems via coping (not conformity or expansion) motives. Motives did not mediate the relation of DT to cannabis use frequency. DT may be an important target in treatment with students who violate campus cannabis policies.